Aboriginal Employment in 2015: A Year of Negative Results - Oppenheimer, Robert J. (Journal of Aboriginal Economic Development, 2016)
The employment, participation, and unemployment rates for Aboriginal and non-Aboriginals in 2015 are compared with the changes that have occurred, primarily from 2014. The changes in all three of these rates were disappointing for Aboriginals in 2015. The employment and participation rates decreased and the unemployment rate increased. Employment data is examined by gender and age, educational level, provinces, regions and territories and by economic sector.